Edukasi praktik pijat oksitosin terhadap peningkatan kelancaran produksi Air Susu Ibu (ASI) - Fatrin, Tiara; Soleha, Marchatus; Apriyanti, Titin; Sari, Yona; Aryanti , Aryanti (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2022)
Breastmilk is the healthiest diet for infants since it includes all the nutrients they require in the right quantity and composition. The production of a tiny amount of breast milk on the first day after delivery is one of the initial hurdles to breastfeeding. Oxytocin massage is one technique for facilitating the release of breast milk. This movement is performed along the spine (vertebrae) to the fifth and sixth ribs. This massage assists to stimulate the hormone oxytocin, which can relax the mother and facilitate the release of breast milk. The purpose of this community service activity was to promote postpartum mothers' knowledge about oxytocin massage. This program was attended by fifteen postpartum mothers from the independent midwife practice of Husniati Palembang. The average findings of the pre-test (40.5%) and post-test (84%) indicate an increase in knowledge scores as a result of this practical education activity. In conclusion, postpartum mothers were becoming more knowledgeable about oxytocin massage therapy. Health education is supposed to be provided continually as part of this service.